Should I Bike or Should I Drive? Comparative Analysis of Travel Speeds in Montreal - Nicolas Saunier; Vincent Chabin (Findings)
Travel time remains one if not the most important factor for mode choice. Cycling is generally considered to be competitive compared to cars in dense urban areas. This paper compares the travel speeds of both modes in Montreal extracted from crowd-sourced trip data. Although car travel is generally faster than bicycle travel, the difference tends to decrease during peak hours or in downtown areas. More than this general difference, travel speed for a significant proportion of cyclists is higher than for the slowest cars. Temporal variation in bicycle travel speed is also smaller than for cars.